Gas turbine engineering handbook - Boyce, Meherwan P. (Boston : Gulf Professional Pub., 2006)
The Gas Turbine Engineering Handbook has been the standard for engineers involved in the design, selection, and operation of gas turbines. This revision includes new case histories, the latest techniques, and new designs to comply with recently passed legislation. By keeping the book up to date with new, emerging topics, Boyce ensures that this book will remain the standard and most widely used book in this field. The new Third Edition of the Gas Turbine Engineering Hand Book updates the book to cover the new generation of Advanced gas Turbines. It examines the benefit and some of the major problems that have been encountered by these new turbines. The book keeps abreast of the environmental changes and the industries answer to these new regulations. A new chapter on case histories has been added to enable the engineer in the field to keep abreast of problems that are being encountered and the solutions that have resulted in solving them. * Comprehensive treatment of Gas Turbines from Design to Operation and Maintenance. In depth treatment of Compressors with emphasis on surge, rotating stall, and choke; Combustors with emphasis on Dry Low NOx Combustors; and Turbines with emphasis on Metallurgy and new cooling schemes. An excellent introductory book for the student and field engineers * A special maintenance section dealing with the advanced gas turbines, and special diagnostic charts have been provided that will enable the reader to troubleshoot problems he encounters in the field. * The third edition consists of many Case Histories of Gas Turbine problems. This should enable the field engineer to avoid some of these same generic problems.
An overview of gas turbines -- Theoretical and actual cycle analysis -- Compressor and turbine performance characteristics -- Performance and mechanical standards -- Rotor dynamics -- Centrifugal compressors -- Axial-flow compressors -- Radial-inflow turbines -- Axial-flow turbines -- Combustors -- Materials -- Fuels -- Bearings and seals -- Gears -- Lubrication -- Spectrum analysis -- Balancing -- Couplings and alignment -- Control systems and instrumentation -- Gas turbine performance test -- Maintenance techniques -- Case histories -- Appendix : equivalent units.
Includes bibliographical references and index.
Keywords: Gas-turbines -- Handbooks, manuals, etc; Turbines αa gaz -- Guides, manuels, etc; Gasturbines; Electronic books; Handbooks, manuals, etc